Ergonomic Risks and Musculoskeletal Disorders (MSDs) Interventions Among Batik Workers: A Systematic Literature Review - Sarah Salman; Salman Salman; Ahmad Ibrahim Syahrul (Indonesian Journal of Applied Science and Technology, 2026)
The batik industry is an important sector in the Indonesian economy and culture, employing a large workforce in informal positions. However, unergonomic work postures, long working hours, and inappropriate tools are the main causes of the high incidence of musculoskeletal disorders (MSDs) in batik industry workers. This study emphasizes the importance of systematically applying ergonomic principles to improve the health and productivity of batik artisans in Indonesia. This study contributes by comparing the effectiveness of various ergonomic methods in the specific context of the traditional batik industry, which has not previously been systematically discussed, and by evaluating the ergonomic interventions that have been implemented. The method used was a PRISMA-based Systematic Literature Review, which included searching, selection, bibliometric analysis, and qualitative discussion. After being filtered, 19 articles were further analyzed. The study results show that ergonomic methods such as NBM, REBA, and RULA are the most widely used to evaluate work posture and the risk of MSDs. Key findings indicate that the most common complaints occur in the neck, shoulders, back, and wrists. The most effective interventions include improving work equipment according to anthropometry, work posture education, task rotation, and implementing active rest.